Breathing Easy: Understanding Respiratory Tract Infections and Safeguarding Respiratory Health - Shajan , Sandra; S. S, Kiron. (Current Patterns and Factors Associated with Infectious Diseases, 2024)
The respiratory tract, comprising the nose, throat, bronchi, and lungs, acts as a gateway and a fortress. A vast variety of Respiratory Tract Infections (RTI) are caused by microscopic organisms such as viruses, bacteria, and fungi. Middle East Respiratory Syndrome (MERS) is a respiratory illness caused by a virus called the Middle East Respiratory Syndrome Coronavirus, Legionnaires' disease is a condition of severe pneumonia caused by an aerobic gram-negative bacillus called Legionella. Histoplasmosis is a disease caused by the fungus Histoplasma. This chapter explores these respiratory tract infections, delving into the epidemiology, pathogenesis, clinical manifestations, diagnosis, prevention, and treatment of these ailments.